Improved Nutritive Quality and Salt Resistance in Transgenic Maize by Simultaneously Overexpression of a Natural Lysine-Rich Protein Gene, SBgLR, and an ERF Transcription Factor Gene, TSRF1 - Wang, Meizhen (Molecular Diversity Preservation International (MDPI), 2013)
Maize (Zea mays L.), as one of the most important crops in the world, is deficient in lysine and tryptophan. Environmental conditions greatly impact plant growth, development and productivity. In this study, we used particle bombardment mediated co-transformation to obtain marker-free transgenic maize inbred X178 lines harboring a lysine-rich protein gene SBgLR from potato and an ethylene responsive factor (ERF) transcription factor gene, TSRF1, from tomato. Both of the target genes were successfully expressed and showed various expression levels in different transgenic lines. Analysis showed that the protein and lysine content in T(1) transgenic maize seeds increased significantly. Compared to non-transformed maize, the protein and lysine content increased by 7.7% to 24.38% and 8.70% to 30.43%, respectively. Moreover, transgenic maize exhibited more tolerance to salt stress. When treated with 200 mM NaCl for 48 h, both non-transformed and transgenic plant leaves displayed wilting and losing green symptoms and dramatic increase of the free proline contents. However, the degree of control seedlings was much more serious than that of transgenic lines and much more increases of the free proline contents in the transgenic lines than that in the control seedlings were observed. Meanwhile, lower extent decreases of the chlorophyll contents were detected in the transgenic seedlings. Quantitative RT-PCR was performed to analyze the expression of ten stress-related genes, including stress responsive transcription factor genes, ZmMYB59 and ZmMYC1, proline synthesis related genes, ZmP5CS1 and ZmP5CS2, photosynthesis-related genes, ZmELIP, ZmPSI-N, ZmOEE, Zmrbcs and ZmPLAS, and one ABA biosynthesis related gene, ZmSDR. The results showed that with the exception of ZmP5CS1 and ZmP5CS2 in line 9–10 and 19–11, ZmMYC1 in line 19–11 and ZmSDR in line 19–11, the expression of other stress-related genes were inhibited in transgenic lines under normal conditions. After salt treatment, the expressions of the ten stress-related genes were significantly induced in both wild-type (WT) and transgenic lines. However, compared to WT, the increases of ZmP5CS1 in all these three transgenic lines and ZmP5CS2 in line 9–10 were less than WT plants. This study provides an effective approach of maize genetic engineering for improved nutritive quality and salt tolerance.